Development and validation of the organisational cooperation questionnaire - dos Santos, Nuno (2020)
tIntroduction. – Cooperation is an essential framework for the functioning of organisations and society.The limitations of current measures of organisational cooperation led us to construct the measure hereinpresented.Objective. – The paper aims to describe the development and psychometric validation of an organisationalcooperation measure based on how the cooperating members view and experience the cooperationprocess.Method. – Based on relevant literature, the items were built and submitted to a panel of experts andfine-tuning procedures. The instrument (31 items) was applied to 1354 employees in local authori-ties. Exploratory and confirmatory factor analysis were performed (2 sub-samples), as well as validationprocedures through Pearson correlation with the Knowledge Management Questionnaire.Results. – Results showed good statistical indicators of a 22-items three-factor structure: principles ofcooperative relationship; formal regulation of cooperation; and cooperation focused on organisationalmission. The factors are interpreted theoretically and present high internal consistency. The validationprocess suggests the suitability of the instrument for the population studied.Conclusion. – This instrument can be used as a starting point for organisational intervention whencooperation-intensive processes are relevant. It can be useful to characterize the existing cooperationin organisations and to foster cooperation in organisations, especially in the intended dimensions. Futurestudies can apply the instrument to various sectors of activity. It will also be worth studying cooperationin its relationship with other organisational variables, namely those concerning cooperation-intensiveprocesses.